Discontinuation Rate of Intrauterine Device and Associated Factors Among Women in the Last One Year in Angacha District, Southern Ethiopia - Mulatu A; Mathewos Oridanigo E; Markos M (Dove Medical Press, 2023)
Alemu Mulatu,1 Eyassu Mathewos Oridanigo,2 Melese Markos3 1Kembata Tembaro Zone Health Department, Durame, Ethiopia; 2Department of Nursing, College of Medical and Health Sciences, Wachemo University, Durame Campus, Durame, Ethiopia; 3Department of Midwifery, College of Medical and Health Sciences, Wachemo University, Durame Campus, Durame, EthiopiaCorrespondence: Eyassu Mathewos Oridanigo, Tel +251911598052 ; +251986973832, Email eyumathi@gmail.comBackground: Discontinuation of intrauterine contraceptive device is the phenomenon of starting a contraceptive method and then ending it within one year of its use. Discontinuation of an intrauterine contraceptive method often leads to unintended pregnancy; this tips to potentially unsafe abortions and unintended births. Even though Ethiopian government gives an attention to long acting reversible contraceptives, especially IUCD, there are no recent studies conducted in the study area. Thus, this study aimed to assess the discontinuation rate of IUCD and associated factors among women in the last one year in Angacha District, southern Ethiopia.Methods: A community-based cross-sectional study was conducted from June 22 to July 22, 2020. Multistage sampling was used to select a total of 596 women who used IUCD during the last year in the Angacha district. Data were collected using pre-tested structured questionnaires. The collected data were entered into Epidata version 3.1 and exported to SPSS version 23 for analysis. Multivariate logistic regression analysis was carried out to identify factors independently associated with discontinuation IUCD. The significance level was set at a p-value of < 0.05 and AOR with 95% CI was used to interpret the association.Results: In this study, 116(19.5%) women discontinued the use of IUCD in the last year with a 95% CI of 16.3%- 22.5%. Counseling before IUCD insertion [AOR (95% CI) = 2.5(1.03, 6.03)], marital status [AOR (95% CI) = 0.23(0.08, 0.69)], access to IUCD service [AOR (95% CI) = 0.29(0.12, 0.72)], and parity [AOR (95% CI) = 3.69(1.97, 8.84)] were significant with discontinuation of IUCD.Conclusion: The overall magnitude of IUCD discontinuation in the study area was found to be high. Counseling before IUCD insertion and parity were positively associated while marital status of mothers and access to IUCD services were negatively associated with the discontinuation of IUCD.Keywords: Angacha district, discontinuation, intrauterine device, Kembata Tembaro zone